Structural Drivers and Democratic Consequences of Political Violence in Nigeria: A Systematic Literature Review - Oyoru, Rashida Adamu; Birisan, Lawal Yusuf; Towoju, Adedoyin John; Otohinoyi, Samuel (NIU Journal of Social Sciences, 2025)
Political violence remains a central threat to democratic stability in Nigeria since the return to civil rule in 1999. It manifests through voter intimidation, armed thuggery, ballot snatching, targeted assassinations, sectarian mobilization, and institutional manipulation. This systematic literature review synthesizes empirical evidence and theoretical contributions across political science, governance, and security studies to identify the structural drivers and democratic consequences of political violence in Nigeria. Data were derived from peer-reviewed journals, policy documents, books, and institutional reports published between 1999 and 2024, selected based on methodological rigor and thematic relevance. Findings reveal that political violence in Nigeria is driven by entrenched poverty, mass youth unemployment, corruption, prebendal political culture, weak state institutions, identity politics, and an entrenched “sit-tight” elite behavior. Political violence undermines democratic consolidation by reducing voter turnout, distorting electoral outcomes, weakening governance institutions, and enabling the emergence of incompetent leadership. The study concludes that political violence in Nigeria is a systemic governance challenge, not an episodic event, and proposes multidimensional reforms involving institutional strengthening, electoral governance reforms, peacebuilding, youth empowerment, and civic reorientation.